Aberrations in Peripheral Inflammatory Cytokine Levels in Parkinson Disease - Jessica, Jessica; Johan, Johan (International Medical Journal Corp. Ltd, 2024)
Background: The literature on peripheral inflammatory cytokine levels in Parkinson's disease (PD) reveals a multifaceted relationship between immune responses and disease pathology. Early foundational work emphasized the crucial roles of both central and peripheral inflammation in PD progression, positing that immune dysregulation may precede neurodegeneration (Su & J. Federoff, 2014). This perspective is supported by subsequent studies that delve into the role of α-synuclein in sustaining neuroinflammation, highlighting the dual nature of inflammatory processes that can initially appear beneficial yet ultimately lead to neuronal degeneration (Pessoa Rocha et al., 2015). Literature Review: Recent research has further established a correlation between elevated levels of peripheral inflammatory cytokines and the severity of motor symptoms in PD, suggesting that inflammation is not merely a byproduct of the disease but a significant contributor to its clinical manifestations (Diaz et al., 2022). Historical analyses have documented the presence of activated microglia and elevated cytokines in PD patients, linking these findings to the progression of motor symptoms (Heidari et al., 2022). The systemic nature of inflammation in PD has been underscored by studies that connect peripheral immune responses to central neuroinflammatory processes, indicating that PD affects various bodily systems (P. Williams et al., 2022). Moreover, the exploration of biomarkers of inflammation in both blood and cerebrospinal fluid (CSF) has illuminated the role of microglial activation and cytokine release in PD progression (Zimmermann & Brockmann, 2022).. Conclusion: In conclusion, the body of literature underscores the significance of peripheral inflammatory cytokines in the pathophysiology of PD. The interplay between central and peripheral immune responses is critical in understanding the disease's progression and symptomatology. Future research should continue to explore these interactions, as they hold potential for developing targeted therapeutic strategies aimed at mitigating inflammation and its effects on PD.